Humanising higher education: transforming the co-curriculum as the core- curriculum at the International Islamic University Malaysia - Sanusi, Zainal Abidin (Global University Network (GUNI), 2019)
Universities formal curriculum are getting more complex and diverse as the world’s issues are getting more complicated and interlinked. In responding to this demand, some subjects turned to be very specific and technical that it may have neglected the purpose of the knowledge to the society. In some cases, the subjects are very commercial-driven and minimal attention is given to the values that need to be inculcated through the subjects. Transformation is needed to humanise the curriculum to bring back the original purpose of universities and education